Viabilidad financiera de importación de láminas de PVC tipo mármol de China a Colombia para la empresa Ferrepunto RZ (2021)
Polyvinyl chloride or PVC is a material used throughout the world in various sectors such as construction, health, electronics and automotive. On this occasion, PVC is especially useful for finishing at home or in industry, through PVC sheets with a marble-like design. This variety of sheets is an interesting option for those who want to give an elegant design to their finishes. For this reason, the Ferrepunto RZ company decided to know the viability of importing this material manufactured in China, since it is not produced in Colombia. To do this, the total cost of the import must be deciphered, in which the value of the merchandise, transportation and nationalization are taken into account, in order to evaluate the technical, economic and financial viability for the import of a product of high demand, use and consumption such as PVC sheets. All negotiations will be possible thanks to international commercial agreements known as Incoterms, in which the characteristics of the contract to be signed between buyer and seller are detailed. These commercial terms have been established to facilitate commercialization between companies and merchants of different nationalities and to be able to carry out these processes without major risks or setbacks.